2012
DOI: 10.1016/j.euroecorev.2012.03.006
|View full text |Cite
|
Sign up to set email alerts
|

The impact of trade on employment, welfare, and income distribution in unionized general oligopolistic equilibrium

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 46 publications
3
43
1
1
Order By: Relevance
“…Indeed, there are a great number of theoretical frameworks that drive a possible relationship between trade positive effect of real trade openness on unemployment was larger than the effects of many labour market institutional variables. Egger and Etzel (2012) investigated the impact of trade on welfare, employment, and income inequality, and they indicated that trade altered rent sharing and affected inequality along multiple dimensions. In open economies, industry factors were less relevant for wage inequality and technological dissimilarity increased gains from trade but decreased employment.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, there are a great number of theoretical frameworks that drive a possible relationship between trade positive effect of real trade openness on unemployment was larger than the effects of many labour market institutional variables. Egger and Etzel (2012) investigated the impact of trade on welfare, employment, and income inequality, and they indicated that trade altered rent sharing and affected inequality along multiple dimensions. In open economies, industry factors were less relevant for wage inequality and technological dissimilarity increased gains from trade but decreased employment.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the impact of labour market and wage bargaining institutions on the aggregate wage may change depending on the level of international competition and, therefore, the degree of openness of an economy. By means of a theoretical model, Egger and Etzel (2012) show that, while firms in more productive industries (and, thus, countries) pay higher wages, exporting lowers per-worker profits because mark-ups on foreign markets are smaller. Accordingly, trade unions are more cautious about the negative effects of wage rises on employment and moderate their wage demands.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Deunionization (defined as a fall in the proportion z of the unionized sectors) implies that the competitive wage increases (as labour demand increases), that the union wage premium falls and that aggregate welfare increases, provided the scale of deunionization (i.e., the fall in the proportion of unionized sectors) is sufficiently wide. Egger and Etzel (2009) somewhat qualify these results of Bastos and Kreickemeier by slightly changing the assumptions in the model. They consider unionization as pervasive in the economy, which gives rise to involuntary unemployment.…”
Section: Globalization and Bargaining When Labour Demand Elasticity Dmentioning
confidence: 68%